Faculty Senate, Agenda, October 16, 2014 - Faculty Senate, Valdosta State University (Valdosta State University Archives and Special Collections, 2014)
Valdosta State University. Faculty Senate, Agenda, October 16, 2014. Michael Noll; James Archibald; Linda Jurczak; Peggy Moch;
Faculty Senate, Agenda, October 16, 2014. 22 pages. 1248511 bytes.
Keywords: Faculty Senate (Valdosta State University); Minutes (Records); Electronic records